Identify potential driver genes for PAX-FOXO1 fusion-negative rhabdomyosarcoma through frequent gene co-expression network mining - Zhan, Xiaohui; Liu, Yusong; Jannu, Asha Jacob; Huang, Shaoyang; Ye, Bo; Wei, Wei; Pandya, Pankita H.; Ye, Xiufen; Pollok, Karen E.; Renbarger, Jamie L.; Huang, Kun; Zhang, Jie (Frontiers in Oncology, 2023)
Rhabdomyosarcoma (RMS) is a soft tissue sarcoma usually originated from skeletal muscle. Currently, RMS classification based on PAX–FOXO1 fusion is widely adopted. However, compared to relatively clear understanding of the tumorigenesis in the fusion-positive RMS, little is known for that in fusion-negative RMS (FN-RMS). Here we explored the molecular mechanisms and the driver genes of FN-RMS through frequent gene co-expression network mining (fGCN) and differential copy number (CN) and expression analysis on multiple RMS transcriptomic datasets. Among the 50 fGCN modules, five are differentially expressed between fusion status. A closer look showed 23% of Module 2 genes are concentrated on chromosome 8 cytobands. Upstream regulators such as MYC, YAP1, TWIST1 were identified for the fGCN modules. Further analysis in a separate dataset confirmed that, comparing to FP-RMS, 59 Module 2 genes show consistent CN amplification and mRNA overexpression, among which 28 are on the identified chr8 cytobands. Such CN amplification and nearby MYC and other upstream regulators (YAP1, TWIST1) may work together to drive FN-RMS tumorigenesis and progression. Up to 43.1% downstream targets of Yap1 and 45.8% of the targets of Myc are differentially expressed in FN-RMS vs. normal comparisons, which also confirmed the driving force of these regulators.